PENGEMBANGAN KOMIK MATEMATIKA BERBASIS KONTEKSTUAL PADA MATERI PERSEGI PANJANG BAGI SISWA KELAS VII - Nendasariruna, Tiadia; Masjudin, Masjudin; Abidin, Zainal (Media Pendidikan Matematika, 2016)
Learning mathematic was not only depended on materiel what was taught, but also it was depended on how materiel source was provided. The interesting of learning media was cause on student and learning characteristic. Therefore this research aimed to develop the valid mathematic comic for students with contextual approach. Contextual approach is a learning concept in which students were brought to think about the real situation or something which had relationship with the experience which was ever found in their daily activity. The type of this research was development research. Development model used was DDD-E, that was decide, design, develop, and evaluate. Data collection technique in this research was with learning module validation, evaluation test, and student respond questionnaire. The sample in this research was the seventh-F grade student at SMPN 11 Mataram. According to result of data analysis, validation test result of media professional was 4,38 with valid category, the test result of materiel professional validation was 4,2 with valid category and classical student learning completeness percentage result was 80% whereas student respond average was 4,22 with high category. It can be concluded that mathematic comic based on contextual on ractangular materiel was valid, effective and practice for seventh grade student at SMPN 11 Mataram.